2018
DOI: 10.1002/smll.201800381
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure Control of Tungsten Oxide Activated by Ni for Ultrahigh‐Performance Supercapacitors

Abstract: Tuning the electron structure is of vital importance for designing high active electrode materials. Here, for boosting the capacitive performance of tungsten oxide, an atomic scale engineering approach to optimize the electronic structure of tungsten oxide by Ni doping is reported. Density functional theory calculations disclose that through Ni doping, the density of state at Fermi level for tungsten oxide can be enhanced, thus promoting its electron transfer. When used as electrode of supercapacitors, the obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…It has been verified that the oxygen vacancies can vary significantly with the doping of different metal elements such as earth metals, [ 107–109 ] rare earths, [ 110–116 ] transition metal, [ 67,117–133 ] or even noble metal. [ 134–139 ] From all the aforementioned classes of metals, the dopants with comparable ionic size and highly soluble feature offers a vast variety of doping element options in MOs.…”
Section: Heterogeneous Ion Doping Strategymentioning
confidence: 99%
“…It has been verified that the oxygen vacancies can vary significantly with the doping of different metal elements such as earth metals, [ 107–109 ] rare earths, [ 110–116 ] transition metal, [ 67,117–133 ] or even noble metal. [ 134–139 ] From all the aforementioned classes of metals, the dopants with comparable ionic size and highly soluble feature offers a vast variety of doping element options in MOs.…”
Section: Heterogeneous Ion Doping Strategymentioning
confidence: 99%
“…Meng et al. prepared Ni‐doped WO 3 nanostructures with different mass loadings of Ni through a facile hydrothermal method . The sample doped with 4.21 at % Ni produced a specific capacitance of 557 F g −1 at 1 A g −1 .…”
Section: Current Advances In Wo3‐based Scsmentioning
confidence: 99%
“…Meng et al prepared Ni-doped WO 3 nanostructures with different mass loadings of Ni through af acile hydrothermal method. [101] The sample doped with 4.21 at %N ip roduced a specific capacitance of 557 Fg À1 at 1Ag À1 .K arthik et al prepared Mn-doped WO 3 nanoparticles through as imple microwave irradiation method. [102] The authors showed that Mn-dopedW O 3 nanoparticles made an excellent electrode for the preparation of high-performance SCs.…”
Section: Wo 3 -Transition-metal-doped Materialsmentioning
confidence: 99%
“…The nanostructures possess many of these features and hence can be the potential candidates for supercapacitor electrodes. The recent work in this direction can be broadly classified into three main categories: 1) carbon‐based materials which include graphene, nanotubes, and activated carbon and their composites; 2) transition metal oxides and metal hydroxides, these include PbO, NiO, MnO 2 , MoO 3 , RuO 2 , CuO, and other metal oxides and metal hydrides such as Co(OH) 2 , Ni(OH) 2 , respectively; and 3) conducting polymers and their composites with various metals and metal oxides . In some of these systems, a significant increase in specific capacitance has been reported.…”
Section: Applications Of Mos2 For Energy Conversion and Storagementioning
confidence: 99%